Management of Severe Attacks of Ulcerative Colitis with New Technologies. (1st November 1990) - Campieri, M; Gionchetti, P; Belluzzi, A; Tampieri, M; Brignola, C; Bertinelli, E; Arienti, V; Iannone, P; Miglioli, M; Barbara, L
Abstract : Barium enema and colonoscopy are contraindicated in severe attacks of ulcerative colitis because of the possibility of toxic megacolon and perforation. The authors have assessed abdominal ultrasound in 38 patients with severe ulcerative colitis. Ultrasound revealed bowel wall thicknesses ranging from 3.9 to 9.2 mm (mean 7.7) extending the whole length of the colon, to the transverse colon, and to the descending colon, respectively, in 18, 10 and eight patients. The degree of bowel thickening was related to the severity of inflammation based on clinical, sigmoidoscopic and histological evaluation. In two patients, ultrasound showed a thin bowel wall distended without motility, suggesting the diagnosis of toxic megacolon (confirmed radiologically). An excellent correlation (95%) was found between ultrasound and technetium-99 scanning. Ultrasound might be a reasonable first investigation in the assessment of patients with severe ulcerative colitis.